Power quality monitoring and analysis / Abdul Halim Ramli - Ramli, Abdul Halim (1996)
Power quality issue is becoming increasingly important because of the proliferation of sensitive loads at homes and industries. Power quality problems which were not important previously could now cause the maloperation of equipment that control manufacturing process. Under this situation, the whole production would stop and result in expensive losses. This final report is concern with the findings of the power quality monitoring as was recorded at several selected site/locations in ITM vacinity. From the data collected, event analysis was done to : • Identify the type of event that occurs. • Compare power event summaries with the general equipment performance tolerances (CBEMA) curve. • Extract events which exceed equipment tolerance for further power quality problem investigation/studies. • Extract events which correlate to any recorded problems. • Summaries the power conditions of the selected site/location. It is intended to present an overall power quality conditions of the monitored site/locations.